ANALISIS KANDUNGAN MIKROPLASTIK DI PANTAI CERMIN - Fauji Ramadhan; Abdurrozzaq Hasibuan (Jurnal Kesehatan, 2023)
As much as 15–40% of all plastic that is dumped into the sea will undergo degradation into microplastics. This research was attempted to analyze the content of microplastics on the coast of Padang and to analyze the correlation between microplastic concentrations with pH, Dissolved Oxygen (DO), temperature, and rainfall. The characteristics of the microplastics analyzed were concentration, color, shape, dimensions, and type of polymer. Illustrations were taken at 9 points with a frequency of 3 times. The concentration of microplastics in the sample is calculated by calculating the number of microplastic particles per unit volume of water or dry sediment mass units. Characteristics of color, shape, and size were analyzed using a microscope, while the type of polymer was analyzed with Fourier Transform Infra Red (FTIR) spectroscopy. The average microplastic concentration in the water illustration is 1.667– 6.667 particles/L and 54.882–84.544 particles/ kilogram in the sediment illustration. The dominant microplastic found was in the form of fiber with a percentage of 95% in the water samples and 79.012% in the sediment samples. The dominant color found is blue with a percentage of 47.619% in the water illustration and 65.432% in the sediment illustration. The most commonly found microplastic size is Large Microplastic (LMP) with a percentage of 76.190% in water samples and 64.198% in sediment samples.